HPLC ANALYSIS OF AMINOACIDS IN THE MERCURY AND CADMIUM TREATED GILL, LIVER AND MUSCLE IN Clarias batrachus: Life Science-Environmental Toxicology - J.SELVANATHAN; KUMAR VANNAM, DINESH; S.VINCENT (International Journal of Life Science and Pharma Research, 2013)
High performance liquid chromatography (HPLC) based separation of individual amino acids was quite revealing and promising field. It has provided the present study with necessary information on amino acid metabolism in the target tissues of the experimental fish Clarias batrachus and also in their relative assimilation, storage and excretion during stress induced response with treated heavy metals like mercury (Hg) and cadmium (Cd). This induction was found to be both as tissue and time specific as it was clearly observed in the morphological changes in gill, liver and muscles. Such differential expression was a great monitor to understand the physiological and cellular adaption's of the fish. The LC50 values were observed at 1.5ppm and 8.0ppm with the treated heavy metals of mercury and cadmium in the fish C.batrachus. HPLC studies revealed changes in the intensity and ranges of amide I, II and III bands in control, mercury and cadmium treated tissues. Amide II band was only the characteristic feature of the treated tissues and it was absent in the control tissues. Amide III band was notably present in the liver tissue exclusively. The presence of these amide band results gave a new direction to the studies on binding site determination of heavy metals like mercury and cadmium.